Estudos preliminares de produção de ácido glucônico a partir de sacarose invertida em biorreator airlift - Lopes, Sidney Magalhães (2011)
The use of sucrose for the production of industrial inputs with higher added value has a great industrial interest, especially glucose and fructose which present many advantages over sucrose in industrial processes. Gluconic acid and its derived salts can be mentioned as second generation products also having wide industrial applicability. This study aimed to perform a preliminary evaluation of the enzymatic process for simultaneous production of gluconic acid and, consequently, its derived salts and a high-fructose syrup from sucrose inverted using glucose oxidase (GOD) enzyme in a concentric draft tube airlift bioreactor with 2.0 working volume. For this propose, the volumetric oxygen transfer coefficient (kLa), obtained under different aeration conditions using solutions with different inverted sucrose concentrations, was firstly evaluated. The results led to a correlation to estimate kLa during the oxidation of glucose to gluconic acid in an airlift bioreactor as a function of air flow rate and medium viscosity. Experimental trials were carried out in batch at 35 °C and pH 5.5 in order to produce gluconic acid with different initial glucose concentrations (20 and 40 g.L-1) in the presence or absence of fructose, and with two different enzyme concentrations. The consumption of glucose and dissolved oxygen was monitored throughout the trials. The kinetic parameters for the process (Vmax, KS and KO) were obtained by fitting of the kinetic model to the experimental values. The results showed that the presence of fructose did not significantly affect the affinity of GOD for glucose due to the small variation of KS, as well as it did not alter Vmax values for equal concentrations of KO showed that, although the dissolved O2 concentration was small compared to that of glucose in the medium, the oxygen was not the limiting factor of the process. The results, even though preliminary, demonstrate the viability of developing a simultaneous production process for gluconic acid and highfructose syrup from inverted sucrose.